The maternal health study: Study design update for a prospective cohort of first‐time mothers and their firstborn children from birth to age ten. Issue 5 (6th May 2021) - Brown, Stephanie J.; Gartland, Deirdre; Woolhouse, Hannah; Giallo, Rebecca; McDonald, Ellie; Seymour, Monique; Conway, Laura; FitzPatrick, Kelly M.; Cook, Fallon; Papadopoullos, Sandra; MacArthur, Christine; Hegarty, Kelsey; et al.
Abstract: Background: Maternal health is critical to the health and well‐being of children and families, but is rarely the primary focus of pregnancy and birth cohort studies. Globally, poor maternal health and the exposure of women and children to family violence contribute to the perpetuation and persistence of intergenerational health inequalities. Objectives: The Maternal Health Study was designed to investigate the contribution of social and obstetric risk factors to common maternal physical and psychological morbidities. Over time, our focus has expanded to include mother‐child pairs and investigation of intergenerational trauma and family violence. Population: A total of 1507 first‐time mothers were recruited in early pregnancy from six public hospitals in Melbourne, Australia, in 2003‐2005. Methods: Women completed questionnaires or telephone interviews in early pregnancy (≤24 weeks); at 32 weeks' gestation; at three, six, nine, 12 and 18 months postpartum; and at four and ten years. At ten years, women and children were invited to participate in face‐to‐face interviews, which included direct assessment of children's cognitive and language development. A wide range of obstetric, social and contextual factors have been measured, including exposure to intimate partner violence (IPV) (1‐year, 4‐year and 10‐year follow‐up). Results: 1507 eligible women were recruited at a mean gestation of 15 weeks. At one year, four years and ten years postpartum, 90.0%, 73.1% and 63.2% of the original cohort took part in follow‐up. One in three women in the study (34.5%) reported exposure to IPV in the first ten years of motherhood: 19% in the first 12 months postpartum, 20% in the year prior to four‐year follow‐up and 18.3% in the year prior to ten‐year follow‐up. Conclusion: The study affords a unique opportunity to examine patterns of maternal and child health and health service use associated with exposure to IPV.